Restaurant Management’s Perspective on Halal Certification: An Exploratory Study in Surabaya, Indonesia - Serli Wijaya; Stanislaus Kenny Notoprasetio; Yoel Jemi Echarystio; Yoel Wibowo (Faculty of Economics, Universitas Sriwijaya, 2018)
As the world’s largest Moslem population of the world, Indonesia has been practicing halal principles in all aspects of the country’s life. In foodservice business sector, halal accreditation acts as the assurance of food and beverage safety and quality that is legitimized by the government or the relevant Moslem religious bodies. This paper aims to examine the knowledge and attitudes of restaurant business operators in Surabaya toward halal certification. The study was exploratory in nature, applying in-depth interviews to eight informants who are owners or managers of the Chinese food restaurants in Surabaya. The findings showed that despite the positive attitude towards halal certification, the level of managers’knowledge about halal certification was still very low due to lack of information they officially received from the relevant organizations regarding the certification.